The absence of environmental awareness in the Kingdom of Saudi Arabia and its impact on green marketing in light of the Kingdom’s vision 2030 - Al-Salmi, Amal Mohammed Saeed Marzouq; Al Otaibi, Faiza Jadi Nahi; Alradhi, Lolowah Fahad Mohammed; Nagi, Amera Mohmmed Ahmed (Journal of Economic, Administrative and Legal Sciences, 2022)
The research aimed to identify the absence of environmental awareness in the Kingdom of Saudi Arabia and its impact on green marketing in achieving the vision of the Kingdom 2030.) students, and the results of the research resulted in a set of results, the most important of which are: The level of environmental awareness among the members of the study sample is high with an arithmetic average of (4.12), and it also showed that the level of awareness of the importance of green marketing among the members of the study sample is high, with an average of (3.90), It also became clear that there is a direct statistically significant relationship at the level (0.05) between environmental awareness and green marketing, and it was found that there were no statistically significant differences at the level of significance (0.05) in the level of environmental awareness and the level of awareness of the importance of green marketing among the members of the study sample due to the difference (gender, age), and in light of these results, the study presented a set of recommendations, the most important of which are: Adopting educational policies aimed at raising awareness and educating members of society in general and university students in particular, in order to pay attention to the environment and ways to preserve it and encourage P to work in the environmental fields and conduct practical research for school and university students and their teachers through rewards and material grants in order to encourage distinguished and new research in this regard and to grant financial privileges to companies committed to implementing the contents of green marketing such as granting soft loans and tax exemptions.